THE INFLUENCE OF LEADERSHIP STYLE AND WELFARE ON THE PERFORMANCE OF VILLAGE SUPERVISORY NON-COMMISSIONED OFFICERS - Dudung Abdurachman (INFOKUM, 2022)
Effective leadership styles and the level of welfare of military personnel can be key factors in improving their performance in training and service tasks in the village environment. This research aims to analyze the influence of leadership style and welfare on the performance of Village Supervisory Officers in the context of the village environment. This research method involves collecting data through questionnaires distributed to Village Development Officers in various villages. The collected data was analyzed using statistical techniques, including regression analysis, to assess the relationship between the leadership style applied by their superiors, the level of welfare of the personnel, and their performance in village development tasks. The results of the research show that leadership style has a positive and significant influence on the performance of village development non-commissioned officer personnel . Meanwhile, welfare has a positive and significant influence on the performance of village supervisory non-commissioned officers. Finally, leadership style and welfare together have a positive and significant influence on the performance of village development non-commissioned officer personnel.